Relative caregivers’ satisfaction towards nursing care of neuro patients in Hospital Universiti Sains Malaysia (USM) - Khairuddin, Nurul Nadzirah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Relative caregivers’ satisfaction has become an important measurement for improving the quality of care for patients in the neuro ICU ward. The current study aimed to assess the level of satisfaction among relative caregivers towards nursing care of neuro patients; to determine the relationship between the satisfactions level among relative caregivers towards nursing care and decision-making related to patient care in neuro ICU, Hospital USM. The study was conducted in the neuro ICU ward, Hospital USM. The data was collected fromJanuary 2022 to July 2022. A cross-sectional study was conducted among 80 respondents using the Malay version of Family Satisfaction Intensive Care Unit (FS-ICU) questionnaire. Statistical analysis was conducted using descriptive statistics and the Pearson correlation test. As a result, the participants showed the highest mean score of 9.04 (SD=0.55) as a majority of data. There was a significant correlation between the satisfactions level among relative caregivers towards nursing care and decision-making related to patient care in the neuro ICU, Hospital USM (r = 0.805, p < 0.001). Hence, nurses play a major role in understanding the relatives’ concerns and needs in determining the best decision-making for the patient. This is because the relatives are the pillar in giving support and hope to the patient.